Factors influencing healthy eating intention among Malaysian adults - Sharkawi, Ismawati (2014)
There is rising awareness among Malaysians on the importance of practising healthy eating habits. However, statistics show that there is severity of the health problems among the Malaysian population. Despite the various programs and campaigns being promoted by the Ministry of Health (MOH) on healthy eating and lifestyles, they seem fail to meet the objectives. In response to this problem, this study in general aims to investigate the healthy eating intention among Malaysian adults. Primary data were collected throughout Malaysia via a self-administered questionnaire and multi-stage stratified sampling based on geographical disaggregation was carried out. The Theory of Planned Behavior (TPB) is extended to incorporate the health motive from Food Choice Questionnaire (FCQ), and two variables from Health Belief Model (HBM) namely the perceived barriers on healthy eating and perceived susceptibility to health risk to better understand the factors influencing respondents’ intention on healthy eating. A total of 1,719 adults responded to the survey and showed high intention towards practicing healthy eating. In food choice motives, the religion factor turned out to be the most important factor, followed by health motives, price, sensory appeal and convenience factors. The findings also indicate that there were four factors derived from the perceived barriers to healthy eating, namely self motivation; cost and physical attribute; lack of time; and unavailable healthy choices. Results from the structural equation modelling showed that all variables significantly influence healthy eating intention. Perceived behavioral control turned out to be the strongest predictor and subjective norm the weakest predictor towards healthy eating intention. The moderation test further indicate that gender, age, income and education level were found to be moderators on the overall model. The empirical findings of this study offer theoretical and practical contributions to the body of knowledge and related parties including food industry players and public health policy makers. In theoretical contribution, the findings of this study add to the literature on utility of the extended TPB in the domain of healthy eating. The results indicate that people’s intentions to eat healthily are better modelled with models that not only include the original dimensions of the TPB, but also incorporate other elements including health motives, perceived barriers and perceived susceptibility. With regard to practical contribution, the study reflects the needs for the food marketers to provide healthy foods which are halal, not expensive, tasty and convenient. The efforts should be supported by the government which may consider offering incentive for food industry players which produce/offer healthy food options. In terms of designing more effective intervention programs on promoting healthier eating behavior, the MOH should focus on changing internal factors including enhancing the people’s self-control and changing their attitude toward healthy eating. Different campaign should be targeted to different group of interest to achieve the desired change of healthy eating habit. To enhance the awareness of risks associated with unhealthy eating practices to strengthen individual’s self control, the campaign should be targeting man and young adults. On the other hand, low income and lower educated people are the target groups in promoting programs to reduce barriers to healthy eating.